Diseño de un Prototipo de Desgranadora para Cacao de 130 kg/h en Fincas Menores a 3 Ha de Gigante (Huila) (2021)
Introduction: Cocoa is a high incidence crop in the municipality of Gigante (Huila); it is an export product; the processes related to harvesting and shelling are manual. Objective: To design a prototype of a 130 kg/h cocoa shelling machine for farms of less than 3 ha in Gigante (Huila). Materials and methods: Taken from Ulrich & Eppinger, it comprises 3 phases (Identification criteria, design and Simulation). Results: A prototype of a shelling machine was designed with a monochassis in AISI 410 steel. A power transmission system with a 3hp motor at 1800 R.P.M and whose maximum supported effort is 78 MPa, using for shelling a centrífugal method. Conclusions: The Prototype established according to the load conditions to which it will be subjected is below the limits of stress, displacement and safety factor, which makes it reliable and functional for shelling.